Ethics of Social Service organizations (part I) - Pelegrí Viaña, Xavier (Cuadernos de Trabajo Social, 2013)
Due to its length, this article is composed of two parts and as a whole it seeks to establish whether to introduce or deepen ethical reflection in social service organizations. This first part is devoted to discovering the characteristics of the organizations in the area of social welfare and how the collective dimension of ethics impacts on them. Then, starting with a set of essential questions, we move to the reasons that require greater analytical rigour and a more consistent practice of the entities for which (or with which) the social intervention professionals work. Although this is the most general part, those elements necessary to frame the second part are addressed. Specific conclusions for the inclusion of the ethical dimension in social services will be proposed in the second part.
Keywords: ethics; organizations; social services; professionals; social work.